PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP HASIL BELAJAR SISWA PADA MATERI PENYAJIAN DATA KELAS V SEKOLAH DASAR - Aulia, Anni; Alim, Jesi Alexander; Putra, Zetra Hainul (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2025)
This research aims to see the influence of the Indonesian Realistic Mathematics Education (PMRI) approach on student learning outcomes in class V data presentation material at SDN 158 Pekanbaru. This type of research is research with a quantitative approach and uses quasi-experimental methods. The design in this research is a nonequivalent control group design, namely using two classes, namely class V B as the experimental class and V A as the control class which was chosen randomly. The experimental class will be given PMRI approach learning treatment and the control class will receive conventional learning treatment. This study provides a pretest before receiving treatment and provides a posttest after receiving treatment. Based on the results of the hypothesis test data analysis that the researcher carried out, the significance (2-tailed) t-test results obtained for the posttest value for the experimental class and control class were 0.004. Based on these results, a significance value of 0.004 <0.05 was obtained so that Ha was accepted and H0 was rejected. Thus, it can be concluded that there is an influence of the Indonesian Realistic Mathematics Education (PMRI) approach to data presentation material on the learning outcomes of fifth grade elementary school students.